Manipulação cirúrgica da medula espinhal em cães submetidos à hemilaminectomia toracolombar dorsolateral - Souza, Giancarlo Santini de (2010)
The aim of this study was to investigate if surgical manipulation of the spinal cord in dogs submitted to thoracolumbar dorsolateral hemilaminectomy influences the development of neurological and myelographic signs at immediate postoperative time. For this reason, fourteen healthy mongrel dogs were used, weighing from 7 to 10 kilos and submitted to hemilaminectomy between T13 and L1 vertebrae and distributed randomly in three groups, denominated as GI or control (n=4), GII or 15 movements (n=5) and GIII or 30 movements (n=5). The dogs in GI were only submitted to thoracolumbar dorsolateral hemilaminectomy surgical technique, on the left side. The dogs in GII and GIII were submitted to the same procedure as GI, followed by 15 and 30 movements, respectively, over the dorsal, left lateral and ventral surfaces of the spinal cord. Neurological exams were carried out 24 and 72 hours after surgery and after these periods, the dogs were submitted to myelography to evaluate filling and irregular delineation of the contrast line in the subarachnoid space. The myelographic evaluation results in lateral and ventrodorsal positions did not show significant difference, even though there was variation between the groups. In the neurological exam, the animals did not demonstrate neurological deficiencies in any of the days of evaluation at PO. According to the proposed experimental model and the results obtained, it can be concluded that the surgical manipulation of the spinal cord in healthy dogs submitted to thoracolumbar hemilaminectomy does not influence the development of neurological deficiencies at immediate postoperative time and the proposed myelography technique, via cisterna magna, presents limitations in evaluating alterations of the spinal cord at the thoracolumbar region.